Admission Glucose-to-Potassium Ratio as a Predictor of Mortality Risk in Severe Traumatic Brain Injury Undergoing Craniotomy: A Retrospective Cohort Study - Purwoko; Sugeng Budi Santosa; Lichte Christian Purbono (HM Publisher, 2026)
Introduction: Traumatic brain injury (TBI) is a leading cause of death and disability, and case fatality after emergency neurosurgery remains high, creating an urgent need for inexpensive, rapidly available prognostic tools. The admission glucose-to-potassium ratio (GKR) integrates the concurrent hyperglycaemia and hypokalaemia of the neuroendocrine stress response and may outperform either parameter alone; this study analysed its correlation with mortality risk in severe-TBI patients undergoing craniotomy. Methods: A retrospective cohort of 95 adults (18–60 years) with severe TBI (Glasgow Coma Scale ≤8) managed surgically at Dr. Moewardi Regional General Hospital, Surakarta (March–August 2024) was studied by consecutive sampling. GKR was calculated from admission blood glucose (mg/dL) divided by serum potassium (mmol/L); mortality risk was quantified with the MOST score (low 0–30, moderate 31–60, high 61–100). Analyses included Spearman correlation with 95% confidence intervals, Kruskal–Wallis testing with ε², ROC analysis, and multivariable logistic regression. Results: Median GKR was 35.14 (range 23.18–64.14) and rose monotonically across strata (26.94, 35.21, 55.67). GKR correlated with mortality risk (ρ = 0.376, 95% CI 0.19–0.54, p < 0.001), more strongly than glucose (ρ = 0.329, p = 0.001) or potassium (ρ = −0.243, p = 0.018). GKR discriminated high mortality risk with an area under the curve of 0.91 (95% CI 0.82–0.99) at a cut-off of 47.0, and each unit raised the adjusted odds of high risk 1.35-fold (95% CI 1.09–1.66, p = 0.006). Conclusion: Admission GKR is a simple, robust bedside marker for early mortality-risk stratification in severe-TBI craniotomy patients.